(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
. This article provides a comparative analysis of the toponymic systems of Germany and Uzbekistan, focusing on their historical, morphological, and cultural features. German toponyms, often formed through compound structures and productive suffixes such as -bach, -dorf, -burg, -heim, and -feld, reflect geographical and social realities of prehistoric and medieval periods. Similarly, Uzbek toponyms, shaped by multi-dialectal variation, phonetic evolution, and historical influences, represent collective folk creativity and tribal identities. Particular attention is paid to the processes of suffixation, prefixation, semantic shift, and phonetic adaptation that characterize both languages. The study highlights distortions introduced during Russian cartographic practices in Central Asia and contrasts them with the systematic codification of German place names through toponymic dictionaries and linguistic corpora. The analysis demonstrates how geographical names function not only as spatial markers but also as cultural symbols that preserve historical memory, identity, and stylistic nuances. The findings underscore the value of cross-linguistic toponymic studies in understanding national heritage and the interaction between language, geography, and culture.